Policies and practices of child adoption in Nigeria: a review paper (2015)
Child adoption, which could be a socially-responsive gesture or a solution for infertility, is gradually becoming culturally acceptable in Nigeria. This paper focuses on analyzing policies and practices of child adoption in Nigeria. It examines policies regulating adoption practices and explores knowledge and attitude towards child adoption, as well as socio-cultural issues in child adoption practices across Nigeria. Secondary data mainly policy documents, existing studies and reviews from scholars, local and international organizations were explored. Nigeria has a National Child Right Act enacted in 2003 that seeks to regulate the welfare of children including child adoption practices. Despite this legislation, most Nigerians are only aware of the term “child adoption” barely few understand the concept of child adoption and the policy regulating it. More so, a large number of infertile couples are familiar with the term “child adoption”, but various social and cultural factors and misconceptions associated with adoption have impaired its full acceptability as a management option for infertility. Adequate support by social welfare system, non-government organizations and health practitioners involved in infertility management will ease pre-existing fears and socio-cultural misconceptions and allow for improved child adoption practices.